PENGARUH KEPEMILIKAN KELUARGA TERHADAP HUBUNGAN ANTARA ARUS KAS DAN INVESTASI - Afanin Nadia Rachmazada; Agung Juliarto (Diponegoro Journal of Accounting, 2020)
This research aims to examine the effect of family ownership on investment-cash flow sensitivity. It also confirms the non-monotonic (S-shaped) relation between the ownership levels of family shareholders on investment-cash flow sensitivity. The population of this research were manufacturing companies listed on the Indonesian Stock Exchange (IDX) on the year 2013 – 2017 with a total sample of 136. Data collected by using purposive sampling method. Multiple linear regression analysis was used as the primary tool of analysis in this research. The results of this study prove that the presence of a family large shareholder has negative significant influence on the investment-cash flow sensitivity. At low levels of shareholdings, the family ownership has negative influence on investment-cash flow sensitivity. At moderate levels of shareholdings, the family ownership has positive influence on investmen- cash flow sensitivity. While at high levels of shareholdings, the family ownership negatively affect investment-cash flow sensitivity. In other words this research succeed in proving the non-monotonic (S-shaped) relation between the ownership levels of family shareholders and investment-cash flow sensitivity.